Adults Attitudes to Mental Diseases/Patients - Adile Tumer (Muhammed Yıldız, 2019)
The aim of this study was to investigate the attitudes of adults towards mental diseases and patients. In this descriptive and cross-sectional study. The data were collected by face-to-face interviews with 312 adult volunteers from a Family Health Center in a provincial center between 15 March-15 May 2016. Data in this research were collected using Specifications Form and Scale of the Community Attitudes Towards the Mentally. Data were evaluated with SPSS program. Descriptive statistics, Kruskall-Wallis Test and Mann-Whitney U Test were used. 51.3% of the participants were women, mean age of the participants was 39.32±11.51. The mean score of the community mental health ideology subscale was 29.0±4.0, goodwill subscale was 27.8±3.8, fear/exclusion subscale was 6.1±1.7, the mean total score was 63.0±7.3. Women's mean scores of goodwill, fear/exclusion, total scale; it was found that the mean score of the university students who graduated from primary school and high school graduates was significantly higher than those who grew up in urban environment compared to those who grew up in rural environment and these results were statistically significant (p<0.05). It was determined that the women were more likely to accept mental diseases than men, feared more from mental diseases than men, and those who grew up in urban environment had more negative attitudes towards mental diseases than those who grew up in rural environment, and university and high school graduates were more likely to accept mental diseases. It is recommended to determine the views of the society on mental diseases and to provide informative trainings to change the negative views of the society.